2016
DOI: 10.1590/s0102-865020160070000001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of lymph nodes in neck dissection specimens. Morphologic study

Abstract: Brazil. Critical revision, design and supervise all phases of the study. ABSTRACT PURPOSE:To quantify the amount of lymph nodes harvested in modified radical neck dissection. METHODS:Cross-sectional anatomical study conducted in 28 non-preserved cadavers. RESULTS:The mean number of lymph nodes found in each nodal level of the 56 modified radical neck dissections performed were:level IA -1.5 (95% CI: 1.1 -1.8), level IB -2.5 (95% CI: 2.1 -2.9), level IIA -7.2 (95% CI: 6.0 -8.5), IIB level -6.5 (95% CI: 5.5 -7.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…There are an estimated 3–5 lymph nodes contained within level I of the neck, however very few studies have contributed to this knowledge and their anatomy needs to be better identified for surgery optimization and safety ( 10 , 16 - 19 ). The current study aims to validate the current literature by quantifying the lymph nodes of level I of the neck.…”
Section: Introductionmentioning
confidence: 99%
“…There are an estimated 3–5 lymph nodes contained within level I of the neck, however very few studies have contributed to this knowledge and their anatomy needs to be better identified for surgery optimization and safety ( 10 , 16 - 19 ). The current study aims to validate the current literature by quantifying the lymph nodes of level I of the neck.…”
Section: Introductionmentioning
confidence: 99%